Transthyretin cardiac amyloidosis in patients with severe aortic stenosis undergoing transcatheter aortic valve replacement: a single center experience. (3rd October 2022) - Scudeler, L; Gallone, G; Bongiovanni, C; Bruno, F; Landra, F; Andreis, A; Fava, A; Pidello, S; Raineri, C; Giorgi, M; D'Ascenzo, F; Conrotto, F; et al.
Abstract: Background: Even if prevalent among patients with severe aortic stenosis (AS), the clinical suspicion for transthyretin cardiac amyloidosis (ATTR-CA) remains difficult in this subset. Methods: Consecutive severe AS patients undergoing transcatheter aortic valve replacement (TAVR) evaluation at a single center were prospectively included. Those with suspected ATTR-CA based on clinical assessment underwent 99mTc-DPD cardiac scintigraphy. The RAISE score, a novel screening tool with high sensitivity for ATTR-CA in AS, was retrospectively calculated to rule-out ATTR-CA in the remaining patients. Patients were categorized as follow: "ATTR-CA+": patients with confirmed ATTR-CA at 99mTc-DPD cardiac scintigraphy; "ATTR-CA−": patients with negative 99mTc-DPD cardiac scintigraphy or a negative RAISE score; c) "ATTR-CA indeterminate": patients not undergoing ATTR-CA assessment with a positive RAISE score. The characteristics of ATTR-CA+ and ATTR-CA− patients were compared. Results: Of 107 included patients, ATTR-CA suspicion was posed in 13 patients and confirmed in 6. Patients were categorized as follow: 6 (5.6%) ATTR-CA+, 79 (73.8%) ATTR-CA−, 22 (20.6%) ATTR-CA indeterminate. Excluding ATTR-CA indeterminate patients, the prevalence of ATTR-CA was 7.1%. As compared to ATTR-CA− patients, ATTR-CA+ patients were older, had higher procedural risk and more extensive myocardial and renal damage. They had higher left ventricle mass index and lower ECG voltages, translating into a lower voltage to mass ratio. Moreover, bifascicular block was more common. No difference in procedural outcomes and 1-year mortality was observed between groups. Conclusions: Among severe AS patients, ATTR-CA is prevalent and presents with phenotypic features that may aid to differentiate it from lone AS. A clinical approach based on routine search of amyloidosis features may effectively lead to selective 99mTc-DPD cardiac scintigraphy with a satisfactory positive predictive value. Funding Acknowledgement: Type of funding sources: None.